Analisis Kepuasan Kerja Pada Karyawan PT.Digivla Indonesia - Grace Natali; Chirstian Wiradendi Wolor; Marsofiyati Marsofiyati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The psychological and emotional state that a person feels in relation to their job is called job satisfaction. It indicates how satisfied, happy, and content a person is with their work environment. Positive feelings about the job itself, the work environment, relationships with coworkers, pay, promotions, recognition, and other elements of the job can be part of job satisfaction. The method used in this research is descriptive qualitative research method which requires identifying and analyzing the problems found. Data collection techniques through observation, interviews and documentation. The purpose of this study was to analyze and determine employee job satisfaction that occurs at PT Digivla Indonesia. The results of pre-research data on 20 employees show that 30% of employees are not satisfied with their jobs and 50% are satisfied with their jobs at PT.Digivla Indonesia. The results of the interview show that job satisfaction affects employee performance, this is supported by the Company's efforts to increase job satisfaction and a supportive environment is one of the factors in employee job satisfaction.